2015
DOI: 10.1128/jb.00612-15
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Metalloregulatory Protein SloR from Streptococcus mutans with Its Metal Ion Effectors and DNA Binding Site

Abstract: Streptococcus mutans is the causative agent of dental caries, a significant concern for human health, and therefore an attractive target for therapeutics development. Previous work in our laboratory has identified a homodimeric, manganese-dependent repressor protein, SloR, as an important regulator of cariogenesis and has used site-directed mutagenesis to map functions to specific regions of the protein. Here we extend those studies to better understand the structural interaction between SloR and its operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Transcriptional repression of the sloABC operon exerted by SloR has been thoroughly characterized by one of our laboratories [30, 31, 36]. In one of these studies a conserved SloR-binding palindrome was identified upstream of the mntH gene but the specificity of SloR binding to the mntH promoter region was not explored at that time [31].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional repression of the sloABC operon exerted by SloR has been thoroughly characterized by one of our laboratories [30, 31, 36]. In one of these studies a conserved SloR-binding palindrome was identified upstream of the mntH gene but the specificity of SloR binding to the mntH promoter region was not explored at that time [31].…”
Section: Resultsmentioning
confidence: 99%
“…Herein we present evidence that supports an updated model for SloR binding at this locus, consistent with the direct binding of SloR homodimers to binding sites that span a 72bp region of DNA which includes the −10 and −35 sloABC promoter. In previous work (22), we described a pattern for SloR binding at the sloABC promoter site that involved two SloR dimers binding to two sets of inverted repeats, each 6bp in length and separated by 8bp. Subsequent analysis of the 72bp region upstream of the sloABC operon suggested that, in fact, SloR binds to three distinct but abutting 22bp sites in that region, referred to herein as A, B, and C. Each binding site is comprised of two inverted hexameric repeats with an AATTAA consensus separated by 6bp, thereby defining a putative 6-6-6 motif for SloR binding (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given frequent reports of sequence variation in and around the −35 promoter region within and across prokaryotic species (39). Since promoter strength is, in part, determined by conservation of the −10 and −35 promoter sequences (36) one might expect RNAP to have only moderate binding affinity for the relatively divergent sloR promoter (TATAAT and TATCCA) as compared to RNAP binding at the more highly conserved sloABC promoter (TATATT and TTGACT) (22), and accordingly, weaker transcription from the former as compared to the latter. The results of DNA binding and expression profiling experiments reported herein support these predictions and suggest a role for divergent sloABC and sloR promoter sequences in fine-tuning metal ion transport and minimizing the toxic effects of metal ion hyper-accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations